A Novel Loom for Alacrity of Protected Lawsuit dealings using Cloud Computing Environment - B.V. Subba Rao; J. Rajendra Prasad; D. Kavitha; J. Sirisha; K. Swaroopa Rani (International Journal of Electrical and Computer Engineering (IJECE), 2016)
This paper suggest a well-organized information system for facilitate the litigation procedures Information System courts. The purpose is to decrease the duration of processing cases in courts. The aspiration is to save the time and effort of judges and lawyer. In addition, we make use of the advantages of electronic systems and reducing traffic especially in developed countries. Advanced Encryption Standard is used to encrypt all the manipulated data for each case. All read document are encrypted to attain secure information system Litigation process. This is because the big data for all cases will be stored on cloud environment.